Why does why have a y?

Updated: 9/24/2023
User Avatar

Wiki User

9y ago

Want this question answered?

Be notified when an answer is posted

Add your answer:

Earn +20 pts
Q: Why does why have a y?
Write your answer...
Still have questions?
magnify glass
Related questions

How do you get more stardollars on stardollcom?

hehghfgvffjghgffgh97b74e654ge67trfejbfejgwe2grg25w6g2w 3g2w g2wg23g23wg2w32gger5gerg443 4465g4er56g4g4g4g ggtgogk rttgrptkoggrtgr65t6r5rt g4r64tgr4tgtr tg5t4g5g45g g54tg6r4tg 54g65gr654gd5g4fg65ty8tg5687gh5ggh865gh8774t987yhjt9y87jt897jt87j987jt987j98t7j r4h6r4thrh4r634h4h 8h79r9r88t+8h8h98+ d6t4gr6g4r66rgt6r34gr Terry yyyyyyyyyyyyyyyyyyyy iguegeuey yyyyyyyyyyy yyy yyyy yyyy yyyyy yyyyyyyyyyyyyyyyyyyyyyyyyy yyyyyyyyyyyyyyyyyyyyyyyyyyyyy yyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyy yyyyyyyyyyyyyyyyy yyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyyy yyyyyyyyyyyyyyyy yyyyyyyyyyyyyyyyyyyyyyy yyyyyyyyyyyyyyyy y y y y y y y y y y y y y y y y y yy y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y y rfrhgfhfghet57rt748r7wr74r76348r7r6348r5847rtdhcghcb fey7ry78r 6+66696hyhe69ge

What is a -y-y-y-y-y-y-y?

means y ????????

What is y x -y?

(y * x) - y = y * (x - 1)

What is 5y equal to?


What is is the greatest common factor of Y and Y?

GCF(Y, Y) = Y.

What is the implicit differentiation of y equals sin x plus y?

y = sin(x+y) cos( x + y )[(1 + y')] = y' cos(x + y ) + y'cos(x + y ) = y' y'-y'cos( x+ y) = cos( x + y ) y'[1-cos(x+y)]= cos(x+y) y'= [cos(x+y)]/ [1-cos(x+y)]

What is the greatest common factor for Y and Y?

GCF(Y, Y) = Y.

What is y times y to the fifth?


What is the correct expansion of the binomial x plus y to the 6th power?

X + Y⁶X + Y * Y * Y * Y * Y * Y

What does y x y eqeal?

Y squared (Y^2)

What is the value of y in y Y Y?

The answer is 37478482993

What is y squared multiplied by y cubed?

y^2 X y^3 = y^(2 + 3) = y^5 You can only do this if the coefficient 'y' is the same for both terms. Remember y^2 = y X y y^3 = y X y X y Hence y^2 X y^3 = y X y X y X y X y = y^5 Similarly for division/subtraction y^3 / y^2 = y^(3 - 2 ) = y^1 = y The power of '1' is trivial and not normally shown. NB You CANNOT do z^2 X y^3 by adding the indices. z^2 X y^3 is (z^2)*(y^3)